2016
DOI: 10.3390/ijms17111866
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Treatment Assigned for Niemann Pick Type C1 Disease Partly Changes Behavioral Traits in Wild-Type Mice

Abstract: Niemann-Pick Type C1 (NPC1) is an autosomal recessive inherited disorder characterized by accumulation of cholesterol and glycosphingolipids. Previously, we demonstrated that BALB/c-npc1nihNpc1−/− mice treated with miglustat, cyclodextrin and allopregnanolone generally performed better than untreated Npc1−/− animals. Unexpectedly, they also seemed to accomplish motor tests better than their sham-treated wild-type littermates. However, combination-treated mutant mice displayed worse cognition performance compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 69 publications
(94 reference statements)
4
18
0
Order By: Relevance
“…Controls included NPC1 +/+ animals as well as NPC1 -/- mutants, being untreated or received normal saline solution or Ringer’s solution without active substances (“sham-treated”). For a better understanding, sham-treated and untreated mice are designated as “sham-treated” in the following sections of this study, since previous studies did not demonstrate any differences between both groups ( Schlegel et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Controls included NPC1 +/+ animals as well as NPC1 -/- mutants, being untreated or received normal saline solution or Ringer’s solution without active substances (“sham-treated”). For a better understanding, sham-treated and untreated mice are designated as “sham-treated” in the following sections of this study, since previous studies did not demonstrate any differences between both groups ( Schlegel et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described by our group [ 45 ] mice of the sham group were injected like those of the combi group at the various time points with respective volumes of 0.9% NaCl or Ringer’s solution, and were fed with chow without drugs. The current dosage regimen was chosen in accordance to previously published studies [ 20 , 21 , 45 , 46 ]. In addition, Tanaka et al [ 19 ] showed that HPβCD applied at a dose of 4000 mg/kg in Npc1 −/− mice caused the best survival rate when compared to saline.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the lowering effects on hexosylceramides in WT CHO cells suggest unfavorable actions of miglustat, such as adverse reactions. Schlegel et al [40] reported that treatment with miglustat impairs spatial learning in WT mice compared with a sham group. Further basic and clinical studies to clarify this issue are warranted.…”
Section: Discussionmentioning
confidence: 99%